The 2004 Claremont Debate: Lipsey vs. Scriven - Stewart I. Donaldson; Christina A. Christie (The Evaluation Center at Western Michigan University, 2005)
While there is little disagreement about the need for, and value of, program evaluation, there remain major disagreements in the field about best practices. An exchange about the role of randomized control trials in program evaluation practice in educational settings set the stage for the 2004 Claremont Debate. In an effort to seek a deeper understanding of the current dispute, and to possibly discover a middleground or productive resolution, Claremont Graduate University hosted a debate between representatives from both sides.